VALIDITAS PERANGKAT PEMBELAJARAN E-LEARNING BERBASIS EDMODO PADA MATA KULIAH ALJABAR LINEAR - Amalina, Amalina; Putri, Darvi Mailisa; Aswirna, Prima (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The purpose of this study is to describe the validity of Edmodo-based E-learning learning tools in linear algebra courses. Learning tools consist of RPS, Teaching Materials and Final Tests that are developed using the ADDIE model, namely Analysis, Design, Develop, Implementation, and Evaluation. The results of this study are Edmodo-based E-Learning learning tools in linear algebra courses for students of Mathematics Tadris FTK UIN Imam Bonjol Padang. Validation involves four validators, namely 3 mathematics education lecturers and 1 language education expert lecturer using a Likert scale learning tool validation sheet on RPS, Teaching Materials, and Final Tests. The results of the study of validity were stated to be very valid by the validators with the RPS obtaining an average score of 3.63, teaching materials obtained a score of 3.38, and the final test obtained a score of 3.41.